The Concept of Cultural and Educational Space in Pedagogical Discourse - Smolinska, Olesia; Dzyubynska, Khrystyna (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
This article is devoted to the problem of definition of approaches of cultural and educational space on the basis of conceptual accents, depending on the purpose of the research. Such hermeneutic aspects are paid attention to as: the problem of correlation between the concepts of climate, environment and space, which are used in pedagogical discourse with similar meanings. The clarification of the content of the cultural and educational space is vital in the interdisciplinary context of philosophy, cultural studies and sociology, since all these scientific disciplines are involved in the formation of the contents, which circulate in the pedagogical discourse. The article eliminates the criteria for the definitions of cultural and educational space by different authors and generalized formulations, which arise from these criteria. In particular, the distinction is made by the following criteria: the physical organizational factor, the organizational and managerial category, the factor of pedagogical influence, the system of coordinates/ values, the communicative space, the object of philosophical and educational discourse, the factor of the formation of the subjectivity of an individual, circumstances of the reality metaphorization while its wording